To disarm [weapons abolition]. - Kumagai, J.
This article describes how recent events have brought a renewed urgency to halting the spread of massively destructive weapons, whether nuclear, chemical, or biological. The concern of the moment is that these deadly devices not fall into the hands of extremists. There may also be a growing sense that what will ultimately make the world a safer place is to eliminate all weapons of mass destruction permanently. Amid fresh fears of a nuclear, chemical or biological attack, abolition no longer seems a crazy idea
Keywords: Biological weapons; Chemical weapons; Disarmament; Nuclear weapons; Weapons abolition; Weapons of mass destruction